2020
DOI: 10.48550/arxiv.2005.08820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical Impact of Social Networks Infodemic on Defeating Coronavirus COVID-19 Pandemic: Twitter-Based Study and Research Directions

Azzam Mourad,
Ali Srour,
Haidar Harmanani
et al.

Abstract: News creation and consumption has been changing since the advent of social media. An estimated 2.95 billion people in 2019 used social media worldwide. The widespread of the Coronavirus COVID-19 resulted with a tsunami of social media. Most platforms were used to transmit relevant news, guidelines and precautions to people. According WHO, uncontrolled conspiracy theories and propaganda are spreading faster than the COVID-19 pandemic itself, creating an infodemic and thus causing psychological panic, misleading… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Twitter also provides access to a large amount of content in many languages. Along this line, many studies of misinformation on Twitter focused on analyzing the content of tweets to understand Twitter conversion during COVID 19 [26,27,28]. To study the development of conversation around misinformation on Twitter, Singh et al [26], collected five common misinformation related to COVID-19, which are about the virus's origin, vaccine development, flu comparison, heat kills the disease, and home remedies.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Twitter also provides access to a large amount of content in many languages. Along this line, many studies of misinformation on Twitter focused on analyzing the content of tweets to understand Twitter conversion during COVID 19 [26,27,28]. To study the development of conversation around misinformation on Twitter, Singh et al [26], collected five common misinformation related to COVID-19, which are about the virus's origin, vaccine development, flu comparison, heat kills the disease, and home remedies.…”
Section: Related Workmentioning
confidence: 99%
“…Another study on how misinformation content spreads over five months on Twitter was presented in [31]. On a different note, the work in [27] presents a different measure of the tweets' credibility based on user specialty and occupation.…”
Section: Related Workmentioning
confidence: 99%
“…Trust is one of the most critical parameters that generate public's acceptance of the risk communication messages (Balog-Way & McComas, 2020;Jacobsen & Vraga, 2020). The featuring of policy makers and institutions outside of the health in messaging and press can be said to have provided the public with confidence on the preparedness of the public institutions and provide them with a sense of a united national response (Finset et al, 2020;La et al, 2020;Mourad et al, 2020;Zhao et al, 2020). Other studies in the country reported that public rating of the national pandemic response was high with a score of 7 out of 10 (Moosa et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…The early published fact sheet about the COVID-19 misinformation suggested 59% of the sampled pandemic-related Twitter posts are evaluated as fake-news [2]. To address this, a huge amount of tweets is collected to disseminate the misinformation [21,23,27,1]. Understanding the problematic consequences of the fake-news, the online platform providers have started flag COVID-19 related information with an "alert" so the audience could be aware of the content.…”
Section: Introductionmentioning
confidence: 99%